Blockade of interleukin 6 signalling ameliorates systemic insulin resistance through upregulation of glucose uptake in skeletal muscle and improves hepatic steatosis in high‐fat diet fed mice. (12th August 2014) - Yamaguchi, Kanji; Nishimura, Takeshi; Ishiba, Hiroshi; Seko, Yuya; Okajima, Akira; Fujii, Hideki; Tochiki, Nozomi; Umemura, Atsushi; Moriguchi, Michihisa; Sumida, Yoshio; Mitsuyoshi, Hironori; Yasui, Kohichiroh; et al.
Abstract Background & Aims Mice fed high‐fat diet (HFD) demonstrate obesity‐related systemic insulin resistance (IR). Aim of this study is to clarify the role of interleukin (IL)‐6 in IR in vivo focusing on skeletal muscle, adipose tissue and liver. Methods Plasma markers of IR and hepatic IL‐6 signalling were examined in eight‐week HFD feeding C57/BL6 mice. Furthermore, IR‐related molecules in skeletal muscles, adipose tissues and livers were investigated following a single injection of anti‐ IL‐6 receptor neutralizing antibody (MR16‐1) in two‐week HFD feeding mice. To investigate the role of IL‐6 in hepatic steatosis by prolonged HFD, hepatic triglyceride accumulation was assessed in eight‐week HFD feeding mice with continuous MR16‐1 treatment. Results High‐fat diet for both 2 and 8 weeks elevated plasma IL‐6, insulin and leptin, which were decreased by MR16‐1 treatment. A single injection of MR16‐1 ameliorated IR as assessed by glucose and insulin tolerance test, which may be attributable to upregulation of glucose transporter type 4 via phosphorylation of AMP‐activated protein kinase as well as upregulation of peroxisome proliferator‐activated receptor alpha in livers and, particularly, in skeletal muscles. MR16‐1 also decreased mRNA expression of leptin and tumour necrosis factor‐alpha and increased that of adiponectin in adipose tissue. High‐fat diet for 8 weeks, not 2 weeks, induced hepatic steatosis and increased hepatic triglyceride content, all of which were ameliorated by MR16‐1 treatment. Conclusions Blockade of excessive IL‐6 stimulus ameliorated HFD‐induced IR in a skeletal muscle and modulated the production of adipokines from an early stage of NAFLD, leading to prevention of liver steatosis for a long term.